The Health Effects of Alpha Lipoic Acid - Armağan Yürük; Aylin Ayaz (Hacettepe University, 2014)
Alpha-lipoic acid is a natural substance found in a variety of foods and also synthesized in the human body. Both alpha lipoic acid and its reduced form dihydrolipoic acid are antioxidants. The antioxidant mechanisms are scavenging free radicals, chelating with metals, regenerating other antioxidants and repairing oxidative damage. It reduces heavy metal toxication by chelating. Lipoic acid supports blood glucose balance by effecting insülin signal pathways. Because of its effects on oxidative stres and glucose balance lipoic acid may prevent diabetic complications and neuro degenerative diseases and their progression.